2013
DOI: 10.1371/journal.pone.0053672
|View full text |Cite
|
Sign up to set email alerts
|

Can Individual and Social Patterns of Resource Use Buffer Animal Populations against Resource Decline?

Abstract: Species in many ecosystems are facing declines of key resources. If we are to understand and predict the effects of resource loss on natural populations, we need to understand whether and how the way animals use resources changes under resource decline. We investigated how the abundance of arboreal marsupials varies in response to a critical resource, hollow-bearing trees. Principally, we asked what mechanisms mediate the relationship between resources and abundance? Do animals use a greater or smaller proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Our analyses revealed that, for all species of arboreal marsupial, the probability of occupancy of an individual hollow-bearing tree was lowest in old growth stands (Figure 2; Appendix 1). Earlier research (Banks et al, 2013) found that the relationship between animal abundance and hollow-bearing tree abundance was positive, but less than 1:1. This was due primarily to a significant increase by all species in the proportional use of hollow-bearing trees where the abundance of this resource was low (Banks et al, 2013).…”
Section: Tree Occupancy and Surrounding Stand Agementioning
confidence: 84%
See 3 more Smart Citations
“…Our analyses revealed that, for all species of arboreal marsupial, the probability of occupancy of an individual hollow-bearing tree was lowest in old growth stands (Figure 2; Appendix 1). Earlier research (Banks et al, 2013) found that the relationship between animal abundance and hollow-bearing tree abundance was positive, but less than 1:1. This was due primarily to a significant increase by all species in the proportional use of hollow-bearing trees where the abundance of this resource was low (Banks et al, 2013).…”
Section: Tree Occupancy and Surrounding Stand Agementioning
confidence: 84%
“…Earlier research (Banks et al, 2013) found that the relationship between animal abundance and hollow-bearing tree abundance was positive, but less than 1:1. This was due primarily to a significant increase by all species in the proportional use of hollow-bearing trees where the abundance of this resource was low (Banks et al, 2013). These earlier results also suggest that other resources or social constraints become limiting for arboreal marsupials under conditions of high hollow-bearing tree availability, such as that found in old growth forest.…”
Section: Tree Occupancy and Surrounding Stand Agementioning
confidence: 84%
See 2 more Smart Citations
“…Reduction in forests containing large, old trees poses pervasive conservation challenges because many species depend on trees with complex structural characteristics that take decades or centuries to develop (Banks et al, 2013). What remains of forested landscapes, including the distribution and extent of remnant old-forest patches and intervening cover types, is a primary driver of the capacity of these landscapes to support populations of old-forest dependent species (Lindenmayer et al, 1999;.…”
Section: Introductionmentioning
confidence: 99%